Association between single nucleotide polymorphism of BMAL1 and bipolar disorder - MIN Wenjiao; SUN Xueli; ZOU Zhili; ZHANG Xu (陆军军医大学学报, 2022)
Objective To identify the association between single nucleotide polymorphism of rhythm gene BMAL1 and bipolar disorder (BD) of clinical characteristics and susceptibility. Methods The case-control study was conducted on 136 outpatients and inpatients with BD(the BD group) and 130 normal controls (the control group) enrolled in the Mental Health Center of West China Hospital of Sichuan University and Psychosomatic Medicine Center of Sichuan Provincial People's Hospital from December 2018 to January 2020. Sixteen single nucleotide polymorphisms (SNPs) of BMAL1 gene were genotyped by SNapShot typing. The levels of TT3, TT4, FT3, FT4 and COR were assayed by electrochemiluminescence immunoassay. Thyroid stimulating hormone (TSH) was measured using ELISA and adrenocor ticotropic hormone (ACTH) was tested by radioimmunoassay. The association between SNPs of BMAL1 and BD of susceptibility and clinical characteristics was statistically analyzed. Results As for the distribution frequencies, allele carriers of rs1022765-C, rs10832022-A and rs6486116-C were significantly higher in BD group than those in control group (P=0.009, 0.005, 0.010). The haplotype analysis showed that the distribution frequency of rs6486116-rs10832020 C-T haplotype in BD group (57.4%) was significantly higher than that in control group (48.5%) (P=0.040); the distribution frequency of rs10832022-rs11022765-rs11022762 G-A-T haplotype was significantly lower in BD group (30.1%) than that in control group (42.7%) (P=0.003). Through multiple logistic regression, the extroversion factor scores of NEO-FFI among patients with different genotypes of rs11022765 were significantly different (P < 0.001). Meanwhile, the incidences of the abnormal HPT axis among patients with different genotypes of both rs10832022 and rs11022765 were also significantly different (P = 0.013, P=0.012). Conclusion SNPs of BMAL1 is associated with the susceptibility of BD, and also associated with clinical phenotypes.